A glimpse inside the lives of the academically talented: What merit scholars and their parents reveal. (2nd July 2020) - Kiewra, Kenneth A.; Rom, Brittany A.
ABSTRACT: To gain a deep and integrative understanding of the conditions associated with academic talent development, a cross-case qualitative study was conducted wherein six National Merit Scholars and their parents were interviewed. Findings from each case study pertaining to home, school, and personal conditions were revealed. Cross-case analysis revealed that the Scholars were raised in enriched two-parent homes with multiple children by well-educated parents. In that home environment, the Scholars showed precocious abilities and acquired positive values about educational success. Children emerged from their early home environments highly motivated, independent, and hard-working. Thereafter, parents had minimal involvement in students' academic success. Schooling played an important role too. Scholars benefited from an assortment of special educational opportunities such as home-schooling and programs for academically gifted. Scholars were also positively influenced by peers, and they engaged in many activities outside academics. Results generally fit with the talent literature with two exceptions: (a) Scholars did not demonstrate a singleness of purpose and (b) parents seemingly had minimal involvement in their child's academic success during the school years.